1999
DOI: 10.1002/(sici)1521-3757(19990419)111:8<1171::aid-ange1171>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Koordinationseigenschaften von Molybdocenalkoxiden – das erste Heterodimetallalkoxid mit Molybdän und Bismut

Abstract: Fluoriert müssen Alkoxidliganden RO− (R = CH(CF3)2) sein, dann lassen sich Verbindungen des Typs [Cp2Mo(OR)2] isolieren. Liefern die Reste R hingegen Elektronen, kann und muß die Mo(OR)2‐Einheit als Ligand für Lewis‐saure Fragmente dienen, wie durch die Isolierung und strukturelle Charakterisierung des ersten Heterodimetallalkoxides mit einem Bi‐ und einem Mo‐Zentrum (1) gezeigt wurde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Recently we have reported the synthesis of the first mixed Bi/Mo alkoxide, representing at the same time the only structurally characterized example of a molecular compound with a discrete oxo linkage of any type between Bi and Mo . All initial attempts to prepare the aforementioned type of species via methods established for the synthesis of other heterometallic alkoxideslike for instance Lewis acid−base reactions of certain alkoxides of Mo and Bi, or by applying the principles of the non-hydrolytic gel formation processhad yielded (in agreement with observations described in the literature 5 ) insoluble, intractable solids.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recently we have reported the synthesis of the first mixed Bi/Mo alkoxide, representing at the same time the only structurally characterized example of a molecular compound with a discrete oxo linkage of any type between Bi and Mo . All initial attempts to prepare the aforementioned type of species via methods established for the synthesis of other heterometallic alkoxideslike for instance Lewis acid−base reactions of certain alkoxides of Mo and Bi, or by applying the principles of the non-hydrolytic gel formation processhad yielded (in agreement with observations described in the literature 5 ) insoluble, intractable solids.…”
Section: Introductionsupporting
confidence: 82%
“…Previous studies have demonstrated the mobility of the ((CH 3 )C 3 H 4 )Mo(CO) 2 complex fragment in alkoxide ligand spheres, and the NMR spectroscopic investigation of 1 provided evidence for a rapid exchange of the OEt ligands at room temperature . Temperature-dependent 1 H NMR spectra of 3 in thf- d 8 revealed that it shows a dynamic behavior in solution, too: the broad singlet at 4.78 ppm (rt) corresponding to the average resonance for the methylene protons of all ethoxy groups shifts to 5.01 ppm on cooling to −10 °C, splitting at −30 °C to give two complex structured signals at −60 °C.…”
Section: Resultsmentioning
confidence: 96%
“…Of all molybdenum bismuth alkoxides known so far, , 6 is certainly the one that is most stable to moisture: it can even be handled in air for short periods of time and thus seemed to be the ideal starting material for experiments with the aim of compositing Mo/Bi/O structures on inert supports, as mentioned in the Introduction. Silica gel was chosen as the supporting material, and treatment with 6 (followed by heating in the presence of O 2 ) could be imagined to give rise to two interesting situations: (i) first of all there was the possibility that such a procedure would lead to dinuclear Mo−O−Bi moieties isolated in a silica matrix, in which case the chemistry of bare Mo−O−Bi linkages could have been studied for the first time; (ii) on the other hand, the acidic Si−OH functions of the silica could be envisaged to induce aggregation and condensation reactions, finally leading to nanoscopic systems on an inert support.…”
Section: Resultsmentioning
confidence: 99%
“…This encourages research with the aim of preparing molecular species containing both Mo and Bi being linked by oxygen-containing, or ideally “pure”, oxo ligands . In this context we have recently reported the first heterometallic Mo/Bi alkoxide complexes. , Their syntheses was achieved starting from molybdenum organyls, where a part of the coordination sphere at Mo is shielded by tightly bound organic ligands: [Cp 2 MoCl 2 ] was chosen to be treated with in situ prepared [Bi(OEt) 3 ] x , yielding [Cp 2 Mo(μ-OEt) 2 Bi(OEt) 2 Cl], 1 , with a Mo and a Bi center being bridged by two ethanolate ligands . Reaction of [((CH 3 )C 3 H 4 )Mo(CO) 2 (CH 3 CN) 2 Cl], 2 me (the suffix “me” denotes the methyl substitution at the allyl ligand), with [Bi(OEt) 3 ] x provided the heterotetranuclear complex [((CH 3 )C 3 H 4 )Mo(CO) 2 (μ-OEt) 3 Bi(μ-OEt) 2 Bi(μ-OEt) 3 Mo(CO) 2 ((CH 3 )C 3 H 4 )], 3 me , in good yields, and treatment with [Bi(OCH 2 CH 2 OCH 3 ) 3 ] 2 , a dinuclear chloro alkoxide [((CH 3 )C 3 H 4 )Mo(CO) 2 (μ-κO,2κO‘-OCH 2 CH 2 OCH 3 ) 2 (μ-Cl)BiCl], 4 me .…”
Section: Introductionmentioning
confidence: 99%